The Effect of Work-Family Conflict and Balancing Strategy towards Wive's Job Satisfaction - Euis Sunarti; Risda Rizkillah; Novy Tri Muktiyah (Journal of Family Sciences, 2020)
This study aims to analyze the effects of work-family conflicts and balancing strategies on job satisfaction felt by families in working husbands and wives. The design of this study was cross-sectional with a sample of 160 wives in families with working wives who have children aged 0-9 years chosen stratified non-proportional random sampling in West Bogor and Central Bogor District, Bogor City. The data collection process carried out using a questionnaire. This study's results indicate that there is a significant negative correlation between work-family conflict and job satisfaction. Besides, theBesidesnificant positive correlation between the strategy of balancing family and work with job satisfaction. Based on the results of the regression test, the data show that work-family conflict and the balancing strategy have an effect on job satisfaction 22.2 percent, and the rest is influenced by other variables not examined. The implications of these results require a broader study for the elaboration of wives' job satisfaction factors.